Next-Generation Retail Integration: A Technical Blueprint for Digital Transformation - Sai Kiran Mannava, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article analysis explores the transformative landscape of retail integration technologies and their pivotal role in shaping the future of commerce. The article examines core integration technologies, including cloud platforms, AI implementations, IoT infrastructure, and blockchain applications, highlighting their collective impact on retail operations. The article presents a holistic view of modern retail technology implementation through a detailed examination of omnichannel integration architecture, data management frameworks, and security protocols. The article investigates the critical aspects of implementation roadmaps, including technical requirements assessment, platform selection criteria, and change management strategies. This article provides valuable insights for organizations navigating the complex landscape of retail technology integration by analyzing current trends, challenges, and opportunities in retail digital transformation. The article emphasizes the importance of a balanced approach between innovation and operational stability while considering the crucial aspects of data security, privacy, and performance optimization in the evolving retail ecosystem.
Keywords: Digital Transformation; Omnichannel Integration; Retail Technology; Data Security; Implementation Framework